Genetic architecture of dusunic, murutic and paitanic ethnic groups of Sabah, Malaysia as revealed by high density genotyping arrays - Yew, Chee Wei (2016)
The native ethnic groups of Sabah are categorized under the 'North Borneo' stock of the Austronesian linguistic family. It is generally believed that the native groups of Northern Borneo are plausibly descendants of the 'Out-of-Taiwan' Austronesian wave of human migration. While there may be some anthropological evidence support for this, the lack of genetic evidence makes the hypothesis inconclusive. As such, this study aimed to unravel and compare the population metrics, genetic structure and genetic relationships of the Northern Borneo indigenous ethnic groups (North Borneans) against Southern China and Southeast Asian populations, and subsequently provide inference of their migration history. Ethical clearance was obtained and blood samples were collected from healthy individuals. A total of 117 individuals representing five indigenous ethnic groups namely Dusun, Rungus, Sonsogon, Sungai-Lingkabau and Murut-Paluan were genotyped with -2.4 million genome-wide single nucleotide polymorphism (SNP) markers. The genotype data were then merged with public datasets i. e. HapMap, Human Genome Diversity Project (HGDP), Singapore Genome Variation Project (SGVP), and Pan-Asian SNP Consortium( PASNP) data to form a comprehensive meta-data set composing of 89 regional and worldwide populations. Population metrics namely decay of linkage disequilibrium, genetic heterozygosity, genetic differentiation (FsT) and phylogeny were analyzed. Next, comparative population genetic structure analysis was performed to determine the genetic gradient among populations, and to assign genetic component and its admixture across the tested populations. Finally, the genetic relationships among populations were inferred by a combinatorial correlation of these outputs. The results showed that the North Borneans were subdivided into three subgroups which were 'Dusun-Rungus', 'Sonsogon-Sungai', and 'Muruts'. The 'Sonsogon-Sungagi' rouping, which is made up of Dusunic and Paitanic-speakingg roup respectively,indicated that the linguistic groupings of the ethnic groups do not necessarily reflect their genetic affinity. Meanwhile,t he North Borneans had reduced heterozygosity and were highly differentiated among themselves. Clustering with principal components clearly depicted that each ethnic group is an independent genetic entity. As a whole, they formed a unique genetic ancestry, which was not found in previous reports. Importantly, they were closest to the non-Negrito Filipinos and the Cosmopolitan Malays of Singapore. However, phylogenetic analysis clustered the North Borneans to the Filipinos and Taiwan Natives, but not to other Island Southeast Asians. On the contrary, the Bidayuhs (West Borneo) was clustered with the Javanese and Temuans. Subsequent estimation of gene flow direction revealed that statistically probable migration event(s) was unidirectional, from North Borneo towards mainland Southeast Asia, but not the reverse. As such, a new hypothesis is postulated that the five ethnic groups descended from Taiwan Natives and Borneo Island served as one of the cross-road for two distinct waves of migration from mainland Southeast Asia and Taiwan, respectively. In conclusion, the findings indicated that Sabah's indigenous population, as a whole, has a unique yet distinctive pool of genetic variants, which are important for anthropological and medical genetic studies